Aleksandar Ranković in Dubrovnik, 1970–1983 - BARIĆ, Nikica (CURRENTS OF HISTORY, 2021)
The paper, using the reports of the Security Service of Socialist Republic of Croatia, discusses how the Security Service conducted surveillance of Aleksandar Ranković and his family while they stayed in their holiday house in Dubrovnik, mostly in the summer season. One of the top officials in communist Yugoslavia, Ranković was ousted from power in 1966. Subsequently, the Yugoslav State Security Service initiated “Action X” whose aim was the surveillance of Ranković and his followers. Ranković’s code name in this project was “Petar”. The reports covering the surveillance of Ranković during his stays in Dubrovnik give various data on him, his family, but they also give insight on the techniques used by the Security Service in its secret surveillance of individuals. Summary: Aleksandar Ranković (1909–1983) was a distinguished Yugoslav communist and revolutionary and close associate of Yugoslav communist leader Tito. Ranković hailed from Serbia and distinguished himself as an organizer of communist interior security services. During the 1960s Yugoslav leadership was in disagreement on the further development of the state. Communist representatives from Slovenia and Croatia opted for wider decentralization of the Yugoslav federation, while Ranković was inclined toward a centralized state. Ultimately, Tito decided to support decentralization, while Ranković was ousted from his position in 1966. To further discredit him, he was also falsely accused of secretly tapping Tito himself. After his downfall, the Yugoslav State Security Service initiated Action X, whose aim was the surveillance of Ranković and his associates. Ranković lived in Belgrade, but he had a holiday home in the Croatian seaside town of Dubrovnik, where he and his family spent summer holidays. Using the reports of the State Security Service of Socialist Republic of Croatia, this paper demonstrates how Action X was conducted while Ranković was staying in Dubrovnik. Clearly, Ranković did not plan any kind of political activity against the regime. By all accounts, he retained respect for President Tito, despite the fact that he eliminated him from the Yugoslav leadership. Furthermore, Ranković was clearly a discrete and reticent person, mostly restrained in his comments of political events. Therefore, reports of Security Service give much more insight into its various surveillance methods and techniques, than about Ranković himself.